Pengaruh Dosis Nitrogen Berbasis Kompos Eceng Gondok dan Waktu Pemeraman Terhadap Pertumbuhan dan Produksi Tanaman Sawi Pakcoy - Lutfiana, Lina; Sutarno, Sutarno; Widjajanto, Didik Wisnu (UNIVERSITAS LABUHANBATU, 2023)
The aim of the study was to evaluate the effect of nitrogen doses based on water hyacinth compost and the fermentation time on the growth and production of pakcoy (Brassica rapa L.). The research was carried out from March 24 to May 29, 2021 at the Greenhouse, Ecology and Plant Production Laboratory, Faculty of Animal and Agricultural Sciences. A 5 x 3 factorial experiment based on a Completely Randomized Design (CRD) with 3 replications was used in this study. The first factor was the dose of nitrogen-based water hyacinth compost (WHC) 0 kg N/ha, K0; 69 kg N/ha equivalent to 4.1 tons of WHC/ha, K1; 138 kg N/ha equivalent to 8.2 tons of WHC/ha, K2; 207 kg N/ ha is equivalent to 12.3 tons of WHC/ha, K3; and 276 kg N/ha is equivalent to 16.4 tons of WHC/ha, K4. The second factor was the fermentation time during the composting process which consists of 21, 28 and 35 days, respectively. Parameters observed were plant height, number of leaves, leaf area, chlorophyll content, shoot and root fresh weight, harvest index. Data were analyzed by analysis of variance and tested further using Duncan's test at 5% level. Based on the research results, it may be concluded that the best performance of pakcoy was achieved at a WHC-based nitrogen dose of 276 kgN/ha and at 35 days.Â Keywords : nitrogen dose, ripening time, pakcoy